(untitled) - Archer, Michael Duane (Hoboken, N.J., 2007)
Written in a straightforward and accessible style, Getting Started in Forex Trading Strategies is a highly visual guide to foreign exchange trading that introduces you to the Codex Method-a proven process that allows you to tailor a trading strategy to your own personal preferences. From here, author Michael Duane Archer outlines his own personal codex-as he guides you through the process of developing yours-and reveals how to use this approach to make, monitor, and exit a trade. Along the way, Archer reveals the best ways to implement your strategy and discusses the importance of consistently keeping trading records.
Keywords: Trao đổi ngoại hối trong tương lai,Dự đoán,Thị trường ngoại hối,Foreign exchange market,Foreign exchange futures,Speculation